Temperature and neuromuscular function - Racinais, S.; Oksa, J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
This review focuses on the effects of different environmental temperatures on the neuromuscular system. During short duration exercise, performance improves from 2% to 5% with a 1 °C increase in muscle temperature. However, if central temperature increases (i.e., hyperthermia), this positive relation ceases and performance becomes impaired. Performance impairments in both cold and hot environment are related to a modification in neural drive due to protective adaptations, central and peripheral failures. This review highlights, to some extent, the different effects of hot and cold environments on the supraspinal, spinal and peripheral components of the neural drive involved in the up- and down-regulation of neuromuscular function and shows that temperature also affects the neural drive transmission to the muscle and the excitation-contraction coupling.